2021
DOI: 10.1021/acscatal.0c05479
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Activity of Co–N–C Catalysts for Chemoselective Hydrogenation of Nitroarenes

Abstract: The production of functionalized anilines by chemoselective hydrogenation of nitroarenes occupies an important position in the chemical industries. Recently, cobalt and nitrogen codoped carbon (Co–N–C) catalysts have been reported to show outstanding catalytic performance in this process, whereas the nature of their active sites is still at the center of intense debate. In this paper, based on the well-controlled experiments on four types of typical Co–N–C materials derived from different methodologies, severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 107 publications
8
64
0
Order By: Relevance
“…SCN − masks the active sites by coordinating with metal centers in the catalyst and deactivate the catalyst. Whereas the CoOx and larger Co nanoparticles are reported to exhibit no effect with the KSCN poisoning test [46,48] . This experiment suggests that the small nanoclusters are present in the catalyst, which further confirms the results obtained from TEM.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…SCN − masks the active sites by coordinating with metal centers in the catalyst and deactivate the catalyst. Whereas the CoOx and larger Co nanoparticles are reported to exhibit no effect with the KSCN poisoning test [46,48] . This experiment suggests that the small nanoclusters are present in the catalyst, which further confirms the results obtained from TEM.…”
Section: Resultssupporting
confidence: 85%
“…Whereas the CoOx and larger Co nanoparticles are reported to exhibit no effect with the KSCN poisoning test. [46,48] This experiment suggests that the small nanoclusters are present in the catalyst, which further confirms the results obtained from TEM. The catalytic poisoning test confirms that the catalytic activity is mainly due to the presence of Co-Nx and Co nanoclusters.…”
Section: Evaluation Of Catalytic Activitysupporting
confidence: 86%
See 2 more Smart Citations
“…It has been reported that the N‐doped carbon shell modified by metal NPs and the embedded metal NPs could be respectively served as catalytic active species for H 2 activation during the hydrogenation reactions [34,37] . Moreover, the strong interaction between embedded metal NPs and N‐doped carbon shell in the well‐defined structure could induce the formation of novel active species such as metal‐N species at the interface [38,39] . Besides, if the embedded metal NPs are bimetallic alloys, the synergistic effect enabled by two different metal components can further enhance the catalytic performance [40–42] .…”
Section: Introductionmentioning
confidence: 99%